can somebody please help with the ans of this ques including steps
Attachments:
![](https://hi-static.z-dn.net/files/d0b/0fb0b34e052adbdd6081ccefbefaa699.jpg)
Answers
Answered by
0
Answer:
1st step
leave the (x-1) (x-2) alone
x^2-9x+14== x^2-2x-7x+14==(x-7)(x-2)
so the first line is in the form of::(x-1) (x-2) (x-2) (x-7) so the (x-2) (x-2) will become (x-2)^2 == x^2+4-4x
and the final line is (x-1) (x^2+4-4x) (x-7)
in the denominator (x^2-3x+2) is in the form of (x-1) (x-2) and from the numerator (x-1) and (x-7) will cancelled
so the rest is (x^2-3x+2) / (x^2+4-4x) ...
hope it helps
pls mark as brainliest
Answered by
3
Answer:
Thank you dear he is always as f.i.re
Attachments:
![](https://hi-static.z-dn.net/files/dca/378c7c1514b2ea60061bd8feff704ef9.jpg)
Similar questions